Syntheses and NMR and XRD studies of carbohydrate–ferrocene conjugates. (5th June 2019) - Peigneguy, Fanny; Allain, Magali; Cougnon, Charles; Frère, Pierre; Siegler, Benjamin; Bressy, Christine; Gohier, Frédéric
Abstract : Carbohydrate–ferrocene conjugates show a splitting of all the 1 H NMR signals of the substituted cyclopentadienyl. XRD of crystals seems to indicate that the R group could be responsible for the splitting of the NMR signals. Abstract : Carbohydrate–ferrocene conjugates were synthesized and showed that the ferrocene entity appeared to be confined to a low volume so that proton NMR spectroscopy revealed 3 to 4 signals for substituted cyclopentadienyl instead of two usually.